An adult with a sinus venosus atrial septal defect and dilated cardiomyopathy. (22nd May 2014) - Oakley, Luke; Foley, Sean; Cox, Justin; Seidensticker, Daniel
Abstract : Dilated cardiomyopathy, heart failure and atrial septal defects are well-recognised entities in isolation, but are rarely seen together. Now that 90% of children with congenital heart disease survive into adulthood, such combinations of disease are increasingly seen in adult cardiology. While most young patients with dilated cardiomyopathy respond well to medical therapy, some do not, and require more invasive management. We describe a 32 year-old man with dilated cardiomyopathy and a sinus venosus-type atrial septal defect associated with a remarkable pulmonary to systemic flow ratio of 5:1. We propose that the atrial septal defect blunted his heart failure symptoms by serving as a 'pop-off' valve and limiting pulmonary congestion. The patient ultimately failed medical management and received a left ventricular assist device. The case is presented along with a discussion of this unique pathophysiology and a brief review of the literature in this rapidly evolving field.